Investigation of Workers’ Sleep Quality in GoleGohar Mineral Industries Co., Sirjan - Zare, Sajad; Shabani, Nader; Babaei Heydarabadi, Akbar; Kazemi Nodeh, Alireza; Asghari, Mehdi; Arab Parizi, Vahid; Imanzad, Masoumeh (Archives of Advances in Biosciences, 2013)
Sleeping is an important physiological process, wielding deep effect on the spiritual and physical health of individuals. The present study has been carried out to investigate workers’ sleep quality in GoleGohar Mineral Industries Co., Sirjan, Iran. This cross-sectional and descriptive-analytical study has been carried out in 2012. The statistical society included 345 workers in of psychological health of workers in Hematite and Pelletizing section in GoleGohar Mineral Industries Co., Sirjan. The sampling method was simple random selection. Pittsburg Sleep Quality Index (PSQI) was applied in the study, with the Cronbach validity of 0.83. Analysis of data was carried out under SPSS 19 software using descriptive and inferential statistics tests. Workers averaged 30.92±4.78 years of age and their working experience averaged 5.47±3.24 years. 82.9 percent of the workers responding to the questionnaire were satisfied with their jobs, and 17.1 percent were not satisfied. Body Mass Index (BMI) for workers averaged 24.5±3.51 Kg/m3.51 Kg/m2 46.9 percent of workers experienced satisfactory sleep and 53.1 percent of them experienced unsatisfactory sleep. The present study has reported workers’ sleep quality in a modest level. With high influence of sleep quality on individual performance and on their general health, and high incidence of workplace events, this aspect of workers’ health should be in the focus of policy-makers and relevant authorities in health sector.